Eficiência produtiva e deposição de produtos fitossanitários em cultivares de soja submetidas à a aplicação de lactofen - Martins, Fernanda Brum (2017)
The presence of weeds along the wheat tillage reduces the availability of water, light, nutrients and it is physical contaminant of the grains after the harvest. Such weeds contribute for the increasing of costs for the agricultural production. To manage against weeds, the chemical control is the most used method, since it allows the intervention in large areas with reduced workforce and speeds on the application. However, it is hampered by the limited availability of selective herbicides to the wheat tillage and increasing occurence of biotypes resisting to the used herbicides. Still, considering the action mechanisms available for the wheat tillage, one must try to find new alternatives, both to manage those plants and also to prevent the selection of new resisting biotypes. The objective of the paper was to quantify the phytotoxity and enzymotic activities of wheat cultivars answering to the oxidative stress caused by saflufenacil herbicide in post-emergence. Also they were studied the dry matter production (DM) and grain profit concerning the herbicide treatment. The results for phytotocity and DM showed the possibility of the use of saflufenacil for the cultivars Tec 10, Tec 03/2013, BRS Parrudo, Fundacep Cristalino, Fundacep 52 and Jadeíte 11, having the gap doses from 7 to 35 g i. a. ha-¹. These cultivars show recovering of symptoms after the herbicide treatment. The application of saflufenacil herbicide does not change the H2O2 proportion, yet, the behavior among the cultivars differs within the times for vegetal matter collecting. Furthermore, the incresing of the dose brings about the antioxidant enzyme activity. The enzymes SOD, APX and CAT from the wheat cultivars which were studied, vary according to the herbicide dose and the time for the vegetal matter collecting. The cultivars BRS Marcante, Jadeíde 11 and ORS Vintecinco show better capacity to do away with the oxidative stress caused by saflufenacil herbicide on the doses 7; 14; 21; 28 and 35 g i. a. ha